2002
DOI: 10.1038/sj.hdy.6800133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and condition factor: a significant relationship in Flemish but not in German populations of the European bullhead (Cottus gobio L.)

Abstract: Although evidence of associations between genetic diversity and fitness in wild species has been published, the lack of a comprehensive review across species and the existence of contradictory results have led to scepticism remaining about its existence and importance in natural populations. In this study, the relationship between genetic diversity at six microsatellite loci and condition factor (a fitness related trait) was investigated at the population level in both Flemish and German populations of the Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 39 publications
2
42
1
4
Order By: Relevance
“…Similar observations were mentioned by earlier workers from this region as well as from other researchers who stated that lengthweight relationship is influenced by physico-chemical (Sunder and Subla, 1984a;Weatherley and Gill, 1987). It has been reported that prevailing environmental conditions (Przybylski, 1996;Tsoumani et al, 2006) and intrinsic factors (Knaepkens et al, 2002) are related to the growth of fish. However, this speculation needs further investigation on other exotic as well as in endemic fish.…”
Section: Effect Of Physico-chemical Features On L-w Relationshipsupporting
confidence: 76%
“…Similar observations were mentioned by earlier workers from this region as well as from other researchers who stated that lengthweight relationship is influenced by physico-chemical (Sunder and Subla, 1984a;Weatherley and Gill, 1987). It has been reported that prevailing environmental conditions (Przybylski, 1996;Tsoumani et al, 2006) and intrinsic factors (Knaepkens et al, 2002) are related to the growth of fish. However, this speculation needs further investigation on other exotic as well as in endemic fish.…”
Section: Effect Of Physico-chemical Features On L-w Relationshipsupporting
confidence: 76%
“…Third, inbreeding depression caused by genetic isolation might lower survival probabilities of upstream individuals and further diminish population sizes (Saccheri et al 1998;Brook et al 2002). Previous work suggests that inbreeding depression occurs in isolated Belgian bullhead populations (Knaepkens et al 2002b), and we are currently investigating whether the same may apply in some of the upstream populations of the River Rye system. Recent results from the grayling Thymallus thymallus (Meldgaard et al 2003) and the cutthroat trout Oncorhynchus clarki clarki (Wofford et al 2005) have shown, respectively, a correlation between numbers of weirs and F ST and between numbers of isolating barriers (some anthropogenic) and genetic diversity (H e ,Â).…”
Section: Discussionmentioning
confidence: 99%
“…David (1998), for example, has asked whether the published studies that demonstrate small positive HFCs might simply reflect a publication bias in favor of positive results (for a discussion, see Coltman and Slate, 2003). It is difficult to generalize about the prevalence of HFC's from individual studies because the strength of HFC's and inbreeding depression may vary with environmental conditions (David and Jarne, 1997;Knaepkens et al, 2002;Myrand et al, 2002).…”
Section: Introductionmentioning
confidence: 99%